Clinical analysis of risk factors for diarrhea associated with enteral nutrition in post-craniocerebral surgery patients - Zhang, Lei; Zhang, Lulu; Zhu, Xiaojie; Xu, Leiming; Zhu, Lin; Zhou, Hai; Yang, Shengkai (Frontiers in Nutrition, 2025)
BackgroundPatients undergoing craniocerebral surgery often require early enteral nutrition (EN) for energy support to improve neurological prognosis. However, diarrhea is a common complication associated with EN that can affect recovery and overall prognosis. This study aims to identify the clinical risk factors for diarrhea in patients receiving EN after undergoing craniocerebral surgery.MethodsThe clinical data of patients hospitalized in the Department of Neurosurgery and Neurosurgical Intensive Care Unit of Binhai County People’s Hospital were retrospectively collected from January 2021 to December 2022. Variables such as sex, age, liquid preservation, infusion duration, pipeline assessment, heating during infusion, infusion rate, post-infusion rounds, and oral care were compared between diarrhea and non-diarrhea groups. Based on the variables obtained from the LASSO regression, multivariate logistic regression was employed to analyze their association with the occurrence of diarrhea. A diagnostic nomogram was constructed to predict the probability of diarrhea in patients receiving EN after craniocerebral surgery.ResultsAccording to the inclusion and exclusion criteria, 141 patients were enrolled in this study, including 50 patients in the diarrhea group and 91 patients in the non-diarrhea group. The following factors were significantly associated with diarrhea: age ≥ 70 years (OR: 2.240; 95% CI 1.110–4.520), no pipeline assessment before EN (OR: 3.807; 95% CI 1.702–7.643), no heating of EN preparations (OR: 3.188; 95% CI 1.853–6.722), no control of normal infusion rate (OR: 1.721; 95% CI 1.136–3.890), no timely post-infusion rounds after EN (OR: 2.260; 95% CI 1.454–5.075), and no oral care during EN. Multivariate logistic regression analysis identified two independent predictors of diarrhea: no heating during EN (OR: 2.135; 95% CI 1.716–5.851) and no oral care during EN (OR: 1.125; 95% CI 1.025–1.652). A diagnostic nomogram based on these two variables was developed to predict the probability of diarrhea in postoperative craniocerebral surgery patients receiving EN. The nomogram demonstrated strong predictive performance, with an AUC of 0.848 (95% CI 0.778 to 0.918).ConclusionVarious factors contribute to the occurrence of diarrhea after receiving EN after craniocerebral surgery. A nomogram incorporating two independent predictors—lack of heating during EN infusion and absence of oral care—exhibited strong predictive ability and may serve as a useful tool for early risk assessment. These findings highlight the importance of incorporating heating protocols and maintaining oral hygiene during EN administration to reduce the risk of diarrhea and improve postoperative care outcomes.